IMPLEMENTASI KOMUNIKASI ORGANISASI PEMERINTAH PADA BADAN PERENCANAAN PEMBANGUNAN, PENELITIAN DAN PENGEMBANGAN DAERAH DALAM MENINGKATKAN KINERJA APARATUR SIPIL NEGARA DI PROVINSI SULAWESI SELATAN - Ashara, A. Ayu; Muttaqin Mustari , Andi; Idris, Muhammad (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
This study aims to determine the implementation of government organizational communication at Bappelitbangda in improving the performance of the State Civil Apparatus in the Province of South Sulawesi and to find out how the communication of the performance of the State Civil Apparatus at the Bappelitbangda of the Province of South Sulawesi. This study uses qualitative research methods and descriptive analysis, Data collection uses three techniques, namely observation, interviews and documentation. The results of this study indicate that; 1). Implementation of government organizational communication at Bappelitbangda in improving the performance of the State Civil Apparatus in the Province of South Sulawesi using Max Weber's organizational communication theory. Using this theory, it can be seen that the implementation of organizational communication in the Bappelitbangda of South Sulawesi Province is by holding monthly or annual meetings as a form of the importance of holding meetings held once a month through two-way communication and being open to getting feedback from meeting participants. 2). Communication on the Performance of the State Civil Apparatus at the Bappelitbangda of South Sulawesi Province. Using the theory of Employee Performance according to Sendow. With this theory, it shows that the performance of the State Civil Apparatus in the Bappelitbangda of South Sulawesi Province is good, marked by the existence of a performance assessment based on SOPs (standard operational procedures). SOP can be used as a standard of supervision on each job so that the implementation can be carried out in accordance with the initial objectives. Then efforts were made to improve the quality of employee performance, namely the South Sulawesi Province Bappelitbangda using instruments related to the duties and functions of the South Sulawesi Province Bappelitbangda in planning and controlling regional development by building several information systems, namely e-Planning and esimonev.